1995
DOI: 10.2307/1243888
|View full text |Cite
|
Sign up to set email alerts
|

Household Demand in Rural China: A Two‐Stage LES‐AIDS Model

Abstract: A complete demand system of Chinese rural households is estimated using a twostage LES-AIDS model and pooled provincial and time-series data from 1982 to 1990. For commodity groups (food, clothing, fuel, housing, and other commodities), demand is price-inelastic. Housing and other commodities are luxury goods, while clothing and food are necessities. Within the food group, price elasticities range from -0.005 to -0.63. Expenditure elasticities are lower for grains and higher for meat, tobacco, and alcohol. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
5
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 2 publications
5
83
5
1
Order By: Relevance
“…Therefore, the AIDS model has been chosen in the present study because of its theoretical and practical considerations, and popularity in demand analysis (Blanciforti and Green 1983;Fujii et al 1985;Fulponi 1989;Heien and Wessells 1990;Fan et al 1995;Huang 1999;Wu 1999;Ma et al 2004;Jabarin 2005;Gould and Villarreal 2006). In addition, the estimated coefficients in a linear approximate almost ideal demand system (LA-AIDS) are easy to interpret (Fulponi 1989;Jabarin 2005).…”
Section: Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the AIDS model has been chosen in the present study because of its theoretical and practical considerations, and popularity in demand analysis (Blanciforti and Green 1983;Fujii et al 1985;Fulponi 1989;Heien and Wessells 1990;Fan et al 1995;Huang 1999;Wu 1999;Ma et al 2004;Jabarin 2005;Gould and Villarreal 2006). In addition, the estimated coefficients in a linear approximate almost ideal demand system (LA-AIDS) are easy to interpret (Fulponi 1989;Jabarin 2005).…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In addition, most previous studies using micro-level survey data did not consider zero expenditure on some items (Fan et al 1995;Cai et al 1998;Ma et al 2004;Wang et al 2004Wang et al , 2005, which has been found to lead to bias in estimation (Haines et al 1988;Heien and Wessells 1990;Perali Figure 1 Meat consumption per capita in rural and urban China (1980 and2005). Note: meat consumption refers to the consumption of pork, poultry, beef and mutton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if FAFH expenditure is well-recorded in household surveys, these surveys may not collect data on the quantities of foods consumed away from home, as is the case for the Chinese Rural Household Survey. Due to a lack of price and quantity information, FAFH is often neglected in food demand analyses, such as Fan, Wailes, and Cramer (1995) and Gao, Wailes and Cramer (1996). Thus, both surveys show a similar increasing trend of FAFH in rural China.…”
Section: Food Consumption Biasmentioning
confidence: 98%
“…First, we have upgraded the income elasticities of demand for farm and food 1 These are obtained from international cross-sectional studies conducted by Theil, Chung, and Seale (1989). In the case of China, we obtain the income elasticities of demand from Zhi and Kinsey (1994) and Fan, Wailes, and Cramer (1995). A complete listing of the values used in the present study is provided in Anderson, Dimaranan, Hertel and Martin (1996a, Appendix, products (see footnote 2).…”
Section: Overview Of the Gtap Frameworkmentioning
confidence: 99%